2016
DOI: 10.1016/j.jcyt.2016.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Genetic modification of H2AX renders mesenchymal stromal cell–derived dopamine neurons more resistant to DNA damage and subsequent apoptosis

Abstract: Background Aberrant production of reactive oxygen species (ROS) and its impact on the integrity of genomic DNA have been considered as one of the major risk factors for the loss of dopaminergic neurons in Parkinson’s disease (PD). Stem cell transplantation as a strategy to replenish new functional neurons has great potential for PD treatment. However, limited survival of stem cells post-transplantation has always been an obstacle which has been ascribed to the existence of neurotoxic environment in PD patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Whether the DNA damage response pathway is the main driver of toxicant‐induced cell death in PD models is unknown. However, recent work showed that introducing the Y142F mutation on histone H2A.X, which facilitates the binding of DNA repair factors, protected cells from MPP+‐induced cell death, suggesting that stimulating DNA repair is neuroprotective (Jiang, Huang, Yen, Zubair, & Dickson, 2016).…”
Section: Dna Damage Response and Dna Double‐strand Break Repair In Pdmentioning
confidence: 99%
“…Whether the DNA damage response pathway is the main driver of toxicant‐induced cell death in PD models is unknown. However, recent work showed that introducing the Y142F mutation on histone H2A.X, which facilitates the binding of DNA repair factors, protected cells from MPP+‐induced cell death, suggesting that stimulating DNA repair is neuroprotective (Jiang, Huang, Yen, Zubair, & Dickson, 2016).…”
Section: Dna Damage Response and Dna Double‐strand Break Repair In Pdmentioning
confidence: 99%
“…As an effective treatment for PD, stem cell-based therapies have been rapidly expanding. However, the clinical use of ESCs and NSCs has presented several physiological problems including ethical constraints, teratoma formation, histocompatibility, inadequate tissue supply, low efficiency of differentiation, lineage polarization, and inefficacy of migration toward damaged brain regions (282930). On the other hand, limited survival and being vulnerable to neurodegeneration of post-transplantation of stem cells has been a main problem attributed to neurotoxic factors and deficiencies in trophic factors in PD brain (28).…”
Section: Discussionmentioning
confidence: 99%
“…The H2A.X variant histone (H2AX) is crucial for maintaining nuclear DNA integrity and dictates the cell's decision to undergo DNA repair or apoptosis, and phosphorylation at tyrosine 142 (Y142) is an important determinant of the switch between DNA repair and apoptosis. Jiang et al reported that BMSC-derived dopaminergic neurons expressing H2AX (Y142F) were resistant to DNA damage induced by oxidative toxicity, suggesting that H2AX (Y142F) upregulation may improve the success of stem cell transplantation therapy for PD [ 233 ]. Also, in a PD model, it was reported that inhibiting the expression of the protein kinase leucine rich repeat kinase 2 (LRRK2) by pharmacological or genetic methods increased the resistance to ROS in MSCs [ 234 ].…”
Section: Selecting Appropriate Genes For Transductionmentioning
confidence: 99%
“…As oxidative DNA damage can disrupt neuronal energy homeostasis and induce apoptosis, transplantation of MSCs overexpressing antioxidant and antiapoptotic factors may also slow PD progression. Indeed, BMSCs overexpressing phosphorylated H2AX, which serves to stabilize genomic DNA under oxidative stress, enhanced the apoptotic resistance of BMSC-derived dopaminergic neurons to neurotoxic insult [ 233 ]. In PD that targets the degeneration of dopaminergic neurons, researchers have considered the introduction of NTFs to nourish the remaining neurons to slow or prevent further degeneration of dopaminergic neurons during PD.…”
Section: Gene Transfer Into Mscs For Neurological Disease Treatmentmentioning
confidence: 99%